(untitled) (LIS TODAY, 2024)
This study explores the information needs and seeking behaviors of women faculty members working in pre-university (PU) colleges in the Kalaburagi district of Karnataka, India. Utilizing a mixed-methods approach, the research investigates the primary sources of information, satisfaction levels with library services, and the impact of socio-demographic factors on information-seeking behaviors. The study reveals significant disparities in access to and use of digital resources, influenced by factors such as age, marital status, and educational background. The findings highlight the critical need for enhanced library services, tailored training programs, and policy interventions to support women faculty in their academic and research activities. These insights contribute to the broader discourse on gender and technology in educational settings, emphasizing the importance of equitable information access in promoting gender equality in STEM fields.